Effect of Health Promotion with Audiovisual on Knowledge of the Use of Personal Protective Equipment for Covid-19 in Health Workers - Christine T. Siwi; Suryadi N. N. Tatura; Jimmy Posangi (e-CliniC, 2022)
Abstract: Health workers are very risky to be infected by Covid-19 virus. The use of personal protective equipment (PPE) for Covid-19 can minimize the transmission of Covid-19. This study was aimed to determine the effect of audio-visual health promotion on knowledge of the use of Covid-19 PPE among health workers. This was a pre-experimental study waith one-grup pre test post test design. Data were analyzed univariately as well as bivariately with paired t-test. Respondents were 40 health workers at the Ratahan Health Center, Southeast Minahasa Regency. The activity was started by signing the approval for filling out questionnaires, doing the pretest, then audiovisual health promotion intervention was carried out and continued with filling out the questionnaire posttest. The results showed that before the health promotion about Covid-19 PPE, most respondents had lack of knowledge as many as 35 health workers (87.5%) and after the health promotion was carried out the knowledge of health workers was categorized as good, namely 36 health workers (90%). The paired t-test showed tat the average value of health worker knowledge before the health promotion about Covid-19 PPE was 22.48±1.5, and after the health promotion the knowledge of health workers was increased to 34.0±0.0 with a p-value of 0.0. In conclusion, the audiovisual health promotion about Covid-19 PPE increases the knowledge of health workers.Keywords: personal protective equipment (PPE); health workers; health promotion Abstrak: Tenaga kesehatan (nakes) sangat berisiko terhadap terinfeksi oleh virus Covid-19. Penggunaan alat pelindung diri (APD) Covid-19 dapat meminimalisir penularan Covid-19. Penelitian ini bertujuan untuk mengetahui pengaruh promosi kesehatan dengan audiovisual terhadap pengetahuan penggunaan APD Covid-19 pada nakes. Jenis penelitian ialah pre-eksperimental dengan one-grup pre test post test design. Analisis data menggunakan analisis univariat dan analisis bivariat dengan uji paired t-test. Responden penelitian ini sebanyak 40 nakes di Puskesmas Ratahan, Kabupaten Minahasa Tenggara. Kegiatan dimulai dengan menandatangani persetujuan pengisian kuesioner pretest kemudian dilakukan intervensi promosi kesehatan menggunakan audiovisual, dan dilanjutkan dengan pengisian kuesioner posttest. Hasil penelitian mendapatkan bahwa sebelum diberikan promosi kesehatan tentang APD Covid-19 pengetahuan nakes terbanyak berada pada kategori kurang yaitu 35 orang (87,5%) dan setelah diberikan promosi kesehatan pengetahuan nakes berada pada kategori baik yaitu 36 orang (90%). Hasil analisis bivariat dengan uji paired t-test menunjukkan nilai rerata pengetahuan nakes sebelum diberikan promosi kesehatan sebanyak 22,48±1,5 dan setelah diberikan promosi kesehatan pengetahuan nakes meningkat sebanyak 34,0±0,0 dengan nilai p=0,0. Simpulan penelitian ini ialah promosi kesehatan dengan audiovisual tentang APD Covid-19 berpengaruh dalam meningkatkan pengetahuan tenaga kesehatan.Kata kunci: alat pelindung diri (APD); tenaga kesehatan; promosi kesehatan